2016
DOI: 10.1103/physrevlett.117.098005
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Interparticle Forces and Heterogeneity in 3D Granular Materials

Abstract: Interparticle forces in granular materials are intimately linked to mechanical properties and are known to self-organize into heterogeneous structures, or force chains, under external load. Despite progress in understanding the statistics and spatial distribution of interparticle forces in recent decades, a systematic method for measuring forces in opaque, three-dimensional (3D), frictional, stiff granular media has yet to emerge. In this Letter, we present results from an experiment that combines 3D x-ray dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
93
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(98 citation statements)
references
References 19 publications
(41 reference statements)
5
93
0
Order By: Relevance
“…The skeletal, nonhydrostatic distribution of force on a scale larger than the particle size was firmly established by experiments with optically sensitive discs Dantu, 1957;de Jong and Verruijt, 1969], 3-D X-ray diffraction [Hurley et al, 2016], and later DEM numerical experiments [Cundall and Strack, 1983].…”
Section: Force Chainsmentioning
confidence: 94%
See 1 more Smart Citation
“…The skeletal, nonhydrostatic distribution of force on a scale larger than the particle size was firmly established by experiments with optically sensitive discs Dantu, 1957;de Jong and Verruijt, 1969], 3-D X-ray diffraction [Hurley et al, 2016], and later DEM numerical experiments [Cundall and Strack, 1983].…”
Section: Force Chainsmentioning
confidence: 94%
“…The skeletal, nonhydrostatic distribution of force on a scale larger than the particle size was firmly established by experiments with optically sensitive discs [ Behringer et al ., ; Dantu , ; de Jong and Verruijt , ], 3‐D X‐ray diffraction [ Hurley et al ., ], and later DEM numerical experiments [ Cundall and Strack , ]. These observations were rationalized with the notion of “force chains” [ Antony , ] as illustrated in Figure .…”
Section: Kinematics Of Hydrogranular Mediamentioning
confidence: 99%
“…Finally, at the particle level, the model predicts particle rotations that on average compare well with those obtained in the experiment. Well beyond reproduction, the avatar paradigm affords the ability to see the evolution of interparticle forces, which are currently impossible to obtain from regular experiments, and which are an active area of research for single-crystal spherical particles [24]. Two modeling advancements afford the avatar paradigm higher fidelity: shape and more accurate boundary conditions.…”
Section: A C C E P T E D Mmentioning
confidence: 99%
“…80 In addition, several other techniques not covered by the Focus Issue deserve mention since they provide contact force measurements for hard, frictional particles for which deformations are not directly observable. Using a combination of x-diffraction and X-ray tomography, Hurley et al 81 have successfully measured inter-particle forces for a small sample of non-transparent particles under compression, and at the singleparticle level. Chen et al 82 have shown that it is possible to use two-photon excitation to make pressure measurements within single ruby particles, based on shifts in the fluorescence spectrum.…”
Section: Measuring Inter-particle Forcesmentioning
confidence: 99%